(untitled) (Educação e Pesquisa, 2020)
This article presents the results of the analysis of four drawings produced and described by girls and boys from two indigenous communities in the state of Chiapas, Mexico. These drawings are considered semiotic texts and form a corpus of documents that allow reading and finding certain clues about how those children interpret their world in a semantic field that gives meaning to their everyday environment, the school, in complex contexts that structure their relationship with indigenous communities. With a semiological and ethnographic methodology and grammar, the drawings and the children´s own descriptions allow us to account for images and ideas of themselves, like boys and girls who, in different ways, are part of a community. In this analysis, their discourses and practices are articulated with their identification processes, to understand how these processes of identity creation and configuration occur in their daily lives, from the drawings and ethnographies of their contexts. In summary, it is about looking at one of its foundations, the relationship between community culture and school culture, in different forms of assimilation, change and resistance, under the experience of the Zapatista indigenous autonomy. Based on this approach, the drawings configure the recreation of research tools that aspire to horizontality, so actually these drawings, more than accompanied by a brief description by way of an interview, open a permanent dialogue with girls, boys and their context in constant change.